The Influence of growth mindset and multiple intelligences on elementary students’ self-regulation - Nurul Zikri Filina; Tria Marvida; Dian Erlita; Lindayani Lindayani; Putri Fakhrina Sari (Journal of Integrated Elementary Education, 2026)
This study examines the association between ALEXISTOTO growth mindset, multiple intelligences, and elementary school students’ self-regulation. Self-regulation is a key competency in elementary education, yet it is often treated as a technical learning skill rather than an integrated cognitive and behavioral capacity. Using a quantitative explanatory design, the study involved 239 fifth-grade students from elementary schools in Aceh. Data on growth mindset, multiple intelligences, and self-regulation were collected through structured questionnaires and analyzed using multiple regression analysis. The results show that growth mindset and multiple intelligences together account for a substantial proportion of variance in students’ self-regulation (R² = 0.673, p < 0.001). Growth mindset was the stronger predictor (β = 0.678, p < 0.001), while multiple intelligences also showed a smaller but statistically significant association (β = 0.155, p = 0.024). These findings indicate that students with higher growth mindset scores and more developed multiple intelligences tend to report higher levels of self-regulation. The study provides empirical evidence on the relative contribution of growth mindset and multiple intelligences to self-regulation among elementary students, without implying causal relationships. The findings may inform educational practices aimed at supporting students’ self-regulatory development.